BREAST CANCER AND PREGNANCY - Ch. Dadak; A. D. Makatsariya (Акушерство, гинекология и репродукция)
25 evidenced based clinical practice guidelines for fertility preservation in cancer patients exist. Breast Cancer in Pregnancy is a rare problem but the incidence is growing, because pregnancy will be delayed in elder age groups. Diagnosis of Breast Cancer is often delayed. If there is a mass, you have to do at first an ultrasound and than mammography if it is necessary. A tumor should be biopsied. Each kind of surgery is possible. Sentinel lymphnode dissection is controversial discussed. It is because of the blue dye, because this substance is not allowed during pregnancy. Technetium is allowed, but will be not accepted by the mother, because of fear of radiance. Radiation and hormonal treatment should be postponed after pregnancy. Chemotherapy can be done after 16 week of gestation. Delivery should not be in the first 3 weeks after chemotherapy, because the nadir of white blood cells should not be at the time of delivery to avoid infection. The fetal outcome is quite normal except weight, because of preterm delivery and growth retardation. Termination of pregnancy will not optimize the cancer prognosis. Pregnancy after breast cancer treatment is possible, perhaps with better prognosis, but that can be due to the healthy mother effect. Because the most recurrence are in the first two years, women should wait 2 years and cryopreservation of ovarian tissue, eggs or embryos before chemotherapy should be done.